Phase III study with FOLFIRI + cetuximab versus FOLFIRI + cetuximab followed by cetuximab alone in RAS and BRAF WT mCRC. (30th May 2018) - Pinto, Carmine; Normanno, Nicola; Orlandi, Armando; Fenizia, Francesca; Damato, Angela; Maiello, Evaristo; Tamburini, Emiliano; Di Costanzo, Francesco; Tonini, Giuseppe; Bilancia, Domenico; Corsi, Domenico; Pisconti, Salvatore; et al.
The optimal duration and intensity of first-line therapy in metastatic colorectal cancer patients once they have achieved an objective response is controversial. In a molecularly selected RAS and BRAF wild-type (wt) population, this concern is amplified. Once disease control has been achieved with a combination therapy including an anti-EGFR antibody, further exposure both to cytotoxic drugs and targeted therapy might result only in increased toxicity. In unresectable metastatic RAS and BRAF wt colorectal cancer patients, a deintensified therapy could represent a valuable option that might preserve quality of life. We designed a study to compare FOLFIRI/cetuximab to FOLFIRI/cetuximab for eight cycles followed by cetuximab alone in first-line treatment of RAS and BRAF (wt) metastatic colorectal cancer patients.